Detection of Mycoplasma synoviae and Mycoplasma gallisepticum in chickens by immunohistochemical, PCR and culture methods - Yilmaz, F.; Timurkaan, N.; Kilic, A.; Kalender, H.; Kilinc, U. (Ecole Nationale Veterinaire Toulouse, 2011)
This study aims to determine pathological findings observed in serologically Mycoplasma gallisepticum (MG) and Mycoplasma synoviae (MS) positive chickens and to compare immunohistochemical, PCR and culture methods for the mycoplasmosis diagnosis. For that, clinical findings were recorded in 120 broiler chickens from commercial poultry farms serologically MG (n = 27) and MS (n = 93) positive with the rapid slide agglutination test. Following necropsy, tissue samples of sinus, trachea, lung, air sac and knee joint were examined using culture, PCR, histological and immunohistochemical (IHC) techniques. Clinical, anatomical and histological alterations corresponding to a severe acute inflammation were found in 12, 35 and 45 cases respectively. Single MG positive immunolabelling was observed in 4 cases, mainly in trachea and lungs, strong MS positive labelling, mainly in trachea, air sacs and lungs, in 16 cases whose 6 also exhibited a weak MG staining. The PCR amplification was positive in 14 out of the 16 IHC positive cases for MS (211 bp band) and in all IHC positive cases for MG (302 bp band), leading to high agreement scores (97.8% and 100% respectively) whereas MS and MG positive cultures were found in 12 and 3 cases respectively. The agreement scores between IHC and culture and between PCR and culture were 95.7% for the MS detection and 96.3% for the MG detection. Consequently, it was concluded that PCR and IHC methods offer a better sensitivity than the culture methods and may be used in the diagnosis of avian mycoplasmosis.
Keywords: Broiler chickens; Mycoplasma gallisepticum; Mycoplasma synoviae; diagnostic; serology; immunohistochemistry; PCR; culture; agreement